XML profile for distributed real time systems - Poon, P.; Dillon, Tharam S.; Chang, Elizabeth; Feng, L. (Institute of Electrical and Electronics Engineers (IEEE) Computer Society, 2008)
In this paper. we describe a XML based profile for modeling the semantics of real time systems. We aim to use Real Time Markup Language (RTML) to provide a comprehensive description oftemporal properties for the use in distributed systems communication RTML is derived from a number of specifications including OMG UML Profile in Schedulability. Performance. and Time. In this paper. we discuss the technique that was used to develop RTML semantic model and the important concepts in RTML.